2020
DOI: 10.3389/fimmu.2020.590373
|View full text |Cite
|
Sign up to set email alerts
|

Towards Precision Vaccines: Lessons From the Second International Precision Vaccines Conference

Abstract: Other than clean drinking water, vaccines have been the most effective public health intervention in human history, yet their full potential is still untapped. To date, vaccine development has been largely limited to empirical approaches focused on infectious diseases and has targeted entire populations, potentially disregarding distinct immunity in vulnerable populations such as infants, elders, and the immunocompromised. Over the past few decades innovations in genetic engineering, adjuvant discovery, formul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 82 publications
0
18
0
Order By: Relevance
“…Innate immune memory responses are complex and depend on the age of the exposed, timing of exposure and properties of the stimulus. Of note, while neonatal Mos express similar quantities of TLRs as their adult counterparts ( 55 , 56 ) the downstream consequences of TLR activation are distinct with age ( 8 ). Whether the BCG-induced tolerance to LPS in neonatal Mos observed in our study is related to TLR-mediated epigenetic reprogramming will be an important area of future investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Innate immune memory responses are complex and depend on the age of the exposed, timing of exposure and properties of the stimulus. Of note, while neonatal Mos express similar quantities of TLRs as their adult counterparts ( 55 , 56 ) the downstream consequences of TLR activation are distinct with age ( 8 ). Whether the BCG-induced tolerance to LPS in neonatal Mos observed in our study is related to TLR-mediated epigenetic reprogramming will be an important area of future investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Much remains to be learned about alterations in neonatal immune function following infection/vaccination during this critical period of immune system adaptation and development. Using BCG as a model to characterize distinct trained immunity in newborns may inform discovery and development of novel adjuvants, vaccines and immunotherapies for this vulnerable population ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…Active immunization against specific pathogens in early life is often hampered by impaired initiation, immunogenicity, antibody production and cell-mediated response, requiring highly species-, age-and patient-specific vaccine approaches (23). These concerns of inadequate vaccine responses in newborns may be particularly relevant for preterm infants and Kulkarni-Munje et al showed that although Indian preterm infants mounted adequate systemic immune responses to the majority of antigens of a pentavalent vaccine, diminished immunological memory remained a concern, relative to term infants.…”
Section: Adaptive Immunity and Immunization In Compromised Newbornsmentioning
confidence: 99%
“…Active immunization against specific pathogens in early life is often hampered by impaired initiation, immunogenicity, antibody production and cell-mediated response, requiring highly species-, age- and patient-specific vaccine approaches ( 23 ). These concerns of inadequate vaccine responses in newborns may be particularly relevant for preterm infants and Kulkarni-Munje et al.…”
Section: Adaptive Immunity and Immunization In Compromised Newbornsmentioning
confidence: 99%
“…Apart from clean drinking water and sanitation, vaccination is one of the most effective medical interventions to avert infectious diseases ( 1 , 2 ). Despite the great successes of past revolutions in vaccinology, current vaccine technologies may still provide suboptimal protection in vulnerable populations, such as infants ( 1 ) and the elderly ( 3 ).…”
Section: Introductionmentioning
confidence: 99%